Six-month outcomes and effect of pulmonary rehabilitation among patients hospitalized with COVID-19: a retrospective cohort study - Yaoshan Dun; Chao Liu; Jeffrey W. Ripley-Gonzalez; Ping Liu; Nanjiang Zhou; Xun Gong; Baiyang You; Yang Du; Jiyang Liu; Bo Li; Suixin Liu (Annals of Medicine, 2021)
AbstractBackground Patients appear to maintain sequelae post-coronavirus disease 2019 (COVID-19) affecting daily life and physical health. We investigated the changes in and the effects of pulmonary rehabilitation (PR) on exercise capacity and immunology six months after COVID-19 hospitalization.Methods This retrospective cohort reviewed 233 COVID-19 patients admitted from 17 January 2020 to 29 February 2020. Ninety-eight patients who completed 2-week and 6-month follow-ups and tests were included. Among 98 patients, 27 completed at least five sessions of PR at the First Hospital of Changsha, China, during the 6-month convalescence were allocated to the PR group; the reminder who had not performed any PR were assigned to the control group. The primary outcome was the change in six-minute walk distance (6-MWD) between the 2-week and 6-month follow-ups, which was assessed via analysis of covariance with a covariate of propensity score that adjusted for the potential confounders. Secondary outcomes were the changes in 6-MWD, SARS-CoV-2 immunoglobulins, T-lymphocytes and blood chemistry, which were evaluated via paired tests.Results Participants’ ages ranged from 19 to 84 years (M = 47, standard deviation (SD)=15) 45.9% identified as male. During the 6-month convalescence, 6-MWD increased 27.0%, with a mean [95% CI] of 113 [92–134] m (p < .001). SARS-CoV-2 IgG and IgM decreased 33.3% (p = .002) and 43.8% (p = .009), CD4+ T cells increased 7.9% (p = .04), and the majority of blood chemistry significantly changed. The patients in the PR group acquired a greater increase in 6-MWD than those in control (unadjusted, 194 [167–221] m, p < .001; adjusted, 123 [68–181] m, p < .001), dose-responsiveness of PR on 6-MWD was observed (p < .001). No differences in immunity variables and blood chemistry were observed between groups.Conclusions These findings suggest PR may be a strategy to promote the improvement of exercise capacity after COVID-19.